Investasi Saham di Bursa Efek Indonesia Perspektif Hukum Ekonomi Syariah - Wawan Setiawan; Akhmad Faozan (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
Stock transactions in the capital market were considered as speculative activities so they are prohibited by Islam and not in accordance with the Shari'a because they lead to gambling. This study aims to provide an explanation to potential investors about stock investment law from the perspective of sharia economic law. This research method use a literature study that was used to examine the legal basis of Islamic economics regarding stock investment. The results of the study show that the stock transaction is a muusahamah contract (trade union or partnership). Then buying and selling shares on the Indonesia Stock Exchange is allowed because shares are proof of ownership of a company in the form of assets, the fiqh experts who allow it are Abu Zahrah, Abdurrahman Hasan and Abdul Wahab Khalaf.